![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
若|m-1|+(n-2)²=0,则1/mn+1/(m+1)(n+1)+1/(m+1)(n+1)+……
若|m-1|+(n-2)的平方=0,则1/mn+1/(m+1)(n+1)+1/(m+1)(n+1)+……+1/(m+2011)(n+2011)=_____________...
若|m-1|+(n-2)的平方=0,则1/mn+1/(m+1)(n+1)+1/(m+1)(n+1)+……+1/(m+2011)(n+2011)=___________________
展开
1个回答
展开全部
|m-1|+(n-2)²=0
所以
m=1,n=2
1/mn+1/(m+1)(n+1)+1/(m+1)(n+1)+……+1/(m+2011)(n+2011)
=1/1×2+1/2×3+1/3×4+。。。+1/2012×2013
=1-1/2+1/2-1/3+1/3-1/4+...+1/2012-1/2013
=1-1/2013
=2012/2013
所以
m=1,n=2
1/mn+1/(m+1)(n+1)+1/(m+1)(n+1)+……+1/(m+2011)(n+2011)
=1/1×2+1/2×3+1/3×4+。。。+1/2012×2013
=1-1/2+1/2-1/3+1/3-1/4+...+1/2012-1/2013
=1-1/2013
=2012/2013
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询